Evaluating the Economic Feasibility of Green Hydrogen from Hydropower Surplus Using Alkaline Electrolysis - Untoro, Meidiono; Juangsa, Firman Bagja (ITB Graduate School Conference, 2025)
The growing demand for clean energy and the urgency to achieve net-zero emissions by 2050 have placed green hydrogen at the center of decarbonization strategies. This study presents a techno-economic analysis of hydrogen production using surplus electricity from hydropower, particularly during rainy seasons when generation exceeds grid demand. A capacity-based approach is employed to estimate surplus energy, which is then used to calculate the required electrolyzer capacity and the Levelized Cost of Hydrogen (LCOH). Using a 20.8 MW alkaline electrolyzer operating at a 75% capacity factor, and a specific energy consumption of 56.69 kWh/kg H2, the base case LCOH is found to be 3.41 USD/kg. A sensitivity analysis shows that electricity price and capacity factor are the most influential parameters affecting LCOH, followed by electrolyzer scale and installation year. Results suggest that optimizing these parameters can significantly improve the economic feasibility of green hydrogen production. The findings highlight the potential of utilizing existing hydropower infrastructure to support hydrogen generation in a cost-effective and scalable manner, especially in developing regions with abundant but underutilized renewable resources.